Optimasi Rongga Terhadap Variasi Derajat Kevakuman Sebagai Isolator - Mulyono, M (Jurnal Teknik Industri, 2010)
In the world of industry, insulation materials are often utilized to maintain the temperature,Â either low or high. However, since the insulation materials often need to be thick, thus,Â costly, they are frequently deemed impractical. Therefore, in the attempt to replace the insulationÂ materials, a cavity with low vacuum pressure is opted for. Yet, to attain a total (100%) airfreeÂ cavity is not an easy task. Such, the cavity usually still bears some amount of air pressureÂ which results in natural heat convection through the two surfaces making up the cavity. TheÂ transfer coefficient of natural heat convection (h) is influenced by some factors, such as, the temperatureÂ difference, geometry of the cavity, cavity orientation, and characteristics of the fluid,Â for instance, its pressure, temperature, conductivity, specific gravity (density), and viscosity.Â The purpose of the study is to find answers to the following question: â€œHow do vacuum pressureÂ variation and cavity ratio affect the rate of natural heat convection through the a cavity?â€ PertinentÂ to the question, the study was aimed to find the appropriate value of the vacuum pressurewhich can function well as an insulator. This study is significant in the attempt to lower downÂ the rate of heat transfer taking place in a system vis-Ã -vis the surrounding media. The studyÂ found out that the degree of emptiness of -60 cm Hg and =5.96, results in a lower rate of heatÂ transfer compared with -20 cm Hg and -40 cm Hg. This means that the vacuum pressure ofÂ -60cm Hg bears a bigger thermal resistance than the -20 cm Hg and -40 cm Hg do.